In-silico analysis of pharmacokinetic properties and molecular targets of lignans and terpenes from Bursera microphylla - Torres-Moreno, Heriberto; López-Romero, Julio César; Rodríguez-Martínez, Karen Lillian; Peraza-Figueroa, David Edgardo; Salcido-Gonález, Beatríz Adriana; Oros-Morales, Ailyn; Robles-Zepeda, Ramón Enrique (Ecosistemas y Recursos Agropecuarios, 2024)
Bursera microphylla A. Gray (Burseraceae) is a Mexican medicinal plant with outstanding antiproliferative and antiinflammatory potential in vitro that has been associated with the presence of lignan and triterpenoid compounds, however, the pharmacokinetic properties (absorption, distribution, metabolism, and excretion - ADME) and the possible pharmacological targets of these compounds are unknown. The objective of this study was to establish in-silico the ADME profile of the bioactive metabolites of B. microphylla and to analyze the main molecular targets that are potentially inhibited by these compounds. ADME analysis of the B. microphylla compounds (14 lignans and 10 terpenes) was performed using the SwissADME tool. The in-silico determination of the potential therapeutic target was performed using the SwissTargetPrediction program. In general, the lignans and terpenes of B. microphylla presented a favorable ADME profile. The predictive analysis showed that hinokinin inhibits the dopamine (DAT) and norepinephrine (NET) transporters. For its part, β-caryophyllene recognizes the cannabinoid receptor type 2 (CB2). Compounds with antiproliferative activity such as ariensin, burseran, dihydroclusin, picropoligamain,and burseranin showed high oral bioavailability. All the compounds analyzed showed the ability to inhibit enzymes of hepatic metabolism, such as CYP1A2 and CYP2C19. The acceptable pharmacokinetic and pharmacodynamic properties of the lignans and terpenes of B. microphylla position them as good prospects to be evaluated in animal models of inflammation, analgesia, cancer, and psychiatric diseases. The potential inhibition of CYPs is an aspect that must be considered to avoid adverse reactions in a combination therapy.
Keywords: Bursera microphylla, pharmacokinetics, lignans, terpenes, ADME profile.